SR9009 improves heart function after pressure overload independent of cardiac REV-ERB - Li, Hui; Song, Shiyang; Tien, Chih-liang; Qi, Lei; Graves, Andrea; Nasiotis, Eleni; Burris, Thomas P.; Zhao, Yuanbiao; Sun, Zheng; Zhang, Lilei (Frontiers in Cardiovascular Medicine, 2022)
The core clock component REV-ERB is essential for heart function. Previous studies show that REV-ERB agonist SR9009 ameliorates heart remodeling in the pressure overload model with transaortic constriction (TAC). However, it is unknown whether SR9009 indeed works through cardiac REV-ERB, given that SR9009 might target other proteins and that REV-ERB in non-cardiac tissues might regulate cardiac functions indirectly. To address this question, we generated the REV-ERBα/β cardiac-specific double knockout mice (cDKO). We found that REV-ERB cardiac deficiency leads to profound dilated cardiac myopathy after TAC compared to wild-type (WT) control mice, confirming the critical role of REV-ERB in protecting against pressure overload. Interestingly, the cardioprotective effect of SR9009 against TAC retains in cDKO mice. In addition, SR9009 administered at the time points corresponding to the peak or trough of REV-ERB expression showed similar cardioprotective effects, suggesting the REV-ERB-independent mechanisms in SR9009-mediated post-TAC cardioprotection. These findings established the essential role of REV-ERB in cardiac response to pressure overload and demonstrated the REV-ERB-independent cardioprotective effect of SR9009 upon pressure overload.